Model Mediasi Kepuasan Kerja pada Pengaruh Kompensasi terhadap Kinerja Pegawai Rumah Sakit: Pendekatan SEM-PLS - Rendi Randika; Nofri Hasrianto; Ahmad Redho (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of compensation on employee performance with job satisfaction as a mediating variable at Hospital X Type C in Pekanbaru. Compensation is an important factor in human resource management that not only functions as a financial reward, but also as a form of organizational appreciation for employee contributions. Job satisfaction acts as an intervening variable that bridges the relationship between compensation and employee performance. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The study population was all 110 employees of Hospital X Type C Pekanbaru, with a sample of 86 respondents selected using the proportionate stratified random sampling technique. Data were analyzed using SmartPLS 4.0 through outer model testing, inner model testing, and hypothesis testing. The results showed that compensation had an effect on employee job satisfaction and performance, and job satisfaction also had a positive and significant effect on employee performance. In addition, job satisfaction was proven to mediate the effect of compensation on employee performance through a significant indirect effect. The R-square value showed that the compensation and job satisfaction variables were able to explain variations in employee performance by 46.3%. Improving employee performance is not only influenced by direct compensation, but also through increasing job satisfaction as a mediating mechanism to improve employee satisfaction and performance in a sustainable manner.